Cross-cultural validation of the Brazilian Portuguese version of the Pain Vigilance and Awareness Questionnaire - Bonafé, Fernanda Salloume Sampaio [UNESP]; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (MRE Press, 2018)
Aims: To cross-culturally adapt the Pain Vigilance and Awareness Questionnaire (PVAQ) to the Brazilian Portuguese language, to evaluate its psychometric properties when applied to Brazilian pain-free adults and to adults with different pain profiles, and to compare the PVAQ factor scores of different groups using a new method for calculating the overall scores for vigilance, attention to pain, and awareness of changes in pain. Methods: A total of 1,143 adults (79% women; mean ± standard deviation [SD] age of 38.56 ± 10.73 years) participated. Face validity and content validity of the Brazilian Portuguese version of the PVAQ were tested. The fit of four PVAQ models was evaluated with confirmatory factor analysis (CFA), and the invariance of the model with the best fit was estimated across two independent samples (test sample: n = 732; validity sample: n = 411). The overall scores of the factors pain vigilance, attention to pain, and awareness of changes in pain were calculated by using the regression weight matrix obtained in the CFA. The overall scores between the four pain groups (no pain, n = 334; pain < 3 months, n = 386; recurrent pain ≥ 3 months, n = 244; continuous pain ≥ 3 months, n = 179) were compared. Results: The refined two-factor model of the PVAQ fit best to the sample (χ2/degrees of freedom = 6.095; comparative fit index = 0.926; goodness of fit index = 0.928; root mean square error of approximation = 0.083; average variance extracted > 0.45; composite reliability and Cronbach's alpha > 0.85) and presented strong invariance in independent samples. Individuals with pain presented higher scores on PVAQ factors, and the highest scores were found among individuals with continuous pain. Conclusion: The Brazilian Portuguese version of the PVAQ was found to be adequate and reliable when applied to the sample. The methodologic considerations presented could improve research on pain vigilance and help clinicians assess PVAQ factors among patients.
Keywords: Attention; Awareness; Methods; Scales; Validation studies